Derivation of master equation for a two-level atom driven by squeezed state field - A Daeichian; H Bagheri; M Mirzaee (Iranian Journal of Physics Research, 2021)
On one hand a two-level atom is utilized as a qubit in quantum information technology and on the other hand the light in quantum optics is usually in the squeezed state. These reasons motivated us to explore the dynamic of a two-level atom which is driven by a field in the squeezed state. To this goal, the atom operators and the Heisenberg-Langevin equation have been employed. The master equation which reveals the dynamic of the atom has been derived using some features of the squeezed state and doing some algebra. Finally, the dynamic of the two-level atom which is driven by squeezed state field has been simulated by the derived master equation. Also, the effect of atom parameters on the dynamic has been investigated.